2017
DOI: 10.1080/19485565.2017.1283582
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Linked Immunoassay-Based Quantitative Measurement of Apolipoprotein B (ApoB) in Dried Blood Spots, a Biomarker of Cardiovascular Disease Risk

Abstract: Apolipoprotein B (ApoB) is a strong predictor of cardiovascular disease, which remains the leading cause of mortality in both higher and lower income countries. Here, we adapted an enzyme-linked immunosorbent assay (ELISA) development kit for quantitative determination of ApoB levels in serum and plasma for use with dried blood spots (DBS). After confirming the dilution linearity of the assay for DBS, we measured ApoB in 208 venous DBS samples. Then, using Passing-Bablok regression analysis and Spearman rank c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
7
1
Order By: Relevance
“…The apparent stability of osteocalcin in DBS at room temperature is noteworthy, as osteocalcin has been shown to be unstable in vitro both at room temperature and at 4°C (Banfi & Daverio, ; Garnero et al, ). This suggests that the filter paper matrix protected against degradation, as has been demonstrated previously for other analytes such as TRACP‐5b, hydrolases, and esterases (Eick et al, ; Freeman et al, ). Finally, the results we obtained for the carboxylated osteocalcin standard from Anaspec suggest that the Abcam assay targets both carboxylated and undercarboxylated forms of full‐length osteocalcin (ie, total osteocalcin; no information is provided by the kit manufacturer regarding the specificity of the kit for carboxylated or uncarboxlyated osteocalcin), indicating that the osteocalcin values obtained using this kit can be used as a biomarker of bone formation.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The apparent stability of osteocalcin in DBS at room temperature is noteworthy, as osteocalcin has been shown to be unstable in vitro both at room temperature and at 4°C (Banfi & Daverio, ; Garnero et al, ). This suggests that the filter paper matrix protected against degradation, as has been demonstrated previously for other analytes such as TRACP‐5b, hydrolases, and esterases (Eick et al, ; Freeman et al, ). Finally, the results we obtained for the carboxylated osteocalcin standard from Anaspec suggest that the Abcam assay targets both carboxylated and undercarboxylated forms of full‐length osteocalcin (ie, total osteocalcin; no information is provided by the kit manufacturer regarding the specificity of the kit for carboxylated or uncarboxlyated osteocalcin), indicating that the osteocalcin values obtained using this kit can be used as a biomarker of bone formation.…”
Section: Discussionsupporting
confidence: 72%
“…However, when the vDBS and fDBS values were converted to their plasma‐equivalent values and compared, no obvious bias was observed in the Bland‐Altman plot (Figure D). It is unclear what to attribute the higher fDBS than vDBS values to; we previously observed slightly higher levels of TRACP‐5b in vDBS than fDBS, and attributed this to the generally smaller diameters of the fDBS than vDBS and correspondingly lower analyte concentrations (Eick et al, ; George & Moat, ), but we observed the opposite pattern here.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…Validation samples comprised matched fingerprick DBS (fDBS), venous DBS (vDBS), and plasma samples ('Eugene200 Validation Set') collected from a convenience sample of 189 adults (≥18 years) from the Eugene/ Springfield, Oregon (USA) area between November 2014 and February 2015 as described in detail previously (Eick, Kowal, Barrett, Thiele, & Snodgrass, 2017). All samples were collected in the evening between 5 PM and 9 PM, but exact time of collection was not recorded and, therefore, not considered in the analyses.…”
Section: Samplesmentioning
confidence: 99%
“…Validation samples comprised matched fingerprick DBS (fDBS), venous DBS (vDBS), and plasma samples ("Eugene200 Validation Set" or E2V2) collected from a convenience sample of 182 adults (M to F 76:106; ≥ 18 years) from the Eugene/Springfield, Oregon (USA) area between November 2014 and February 2015 as described in detail previously [16]. IRB approval for this study was obtained from the Committee for the Protection of Human Subjects, University of Oregon (protocol # 7062016.007), and informed consent was obtained from all participants.…”
Section: Samplesmentioning
confidence: 99%